(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2018)
The professional practice of a psychotherapist is constituted by a set of behavior classes that involve characterizing intervention needs, planning, performing, evaluating, improving the intervention, and reporting the findings. The purpose of this study was to identify behavior classes of the professional practice of a behavior-analytic therapist when working with depressive behaviors in the clinical context. Three sources of information were selected (two articles and a book chapter), and eight steps were taken to identify behavior classes and categorize them according to general classes of a clinical intervention. A total of 399 behavior classes names were proposed, with the majority (98%) constituting the general classes “Characterizing needs”, “Planning intervention”, and “Executing intervention”. The proposition of behavior classes increases the probability of their development in formal contexts of teaching. The lack of representativeness of other general classes suggests that producing knowledge about the processes that constitute them is warranted.